Sustaining ocular emergency and trauma services in corona crisis during the era of pan lockdown - Sharma, Suhani; Kochar, Anju; Joshi, Rashmi (International Journal Of Community Medicine And Public Health, 2021)
Background: The impact of covid pandemic and pan lockdown on the ocular trauma and emergency department has proved the importance of ocular trauma services deliverance on national vision statics. The un-availability of ophthalmic services in remote areas and limited resources have large impact on prognostic outcomes of ocular emergencies. The presentation of ocular emergency cases and their demographic pattern is important in planning and programming of national strategy to cope up with and sustain the ocular emergency services during such pandemics. Methods: Retrospective cohort study at tertiary care center. Results: The incidence of ocular trauma was increased in male pediatric age group with most common mode of injury was wooden objects. The prognosis of visual outcome was ill- affected due to late presentation and un-availability of ocular emergency services in remote areas. Conclusions: The strategy of “Reassess-Reinforce-Resume” was proved successful in sustaining the emerging trend of ocular trauma during COVID pan- lockdown.